The Correlation between Efl Anxiety and Students’ Reading Comprehension”. - Rama, Asri Nofa (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2021)
The objective of the current study examined whether there was any significant correlation between foreign language classroom anxiety and students’ reading comprehension. In this regard, hopefully, this study provided English language lecturers to recognize the most provoking factor that affect learning a foreign language, such anxiety and helped students to solve language anxiety to become better English language students. This researcher was conducted at Lakidende University, particularly 32 university students of English Language Teaching Department who enrolled in academic year 2018/2019. The data were obtained from students’ reading comprehension test and questionnaire that is Foreign Language Classroom Anxiety Scale (FLCAS) and to analyze the data this study applied Pearson Correlation analysis. The finding revealed that there was a significant relationship between foreign language classroom anxiety and students’ reading comprehension, p (.061) less than 0.05. Meanwhile, the strength of correlation between reading anxiety and students’ reading comprehension was categorized “moderate” according to table Guidelines of Interpreting Pearson's Correlation Coefficient (r =.381). It might be the fact that most of students frequently experienced moderate level of foreign language classroom anxiety in their reading comprehension class.